Influence of self-efficacy and goal orientation on academic achievements among Chinese junior middle school students - Zou, Yuxue; Mustakim, Siti Salina (Human Resource Management Academic Research Society, 2024)
The aim of this study was to explore factors influencing academic performance. It surveyed 400 junior high school respondents through questionnaire forms and analyzed the results using methods like Spearman rank correlation and Mann-Whitney U. The study found significant positive correlations between self-efficacy in learning ability, approach goals, and mastery goals with academic performance. Significant differences in academic performance were observed based on gender, holding class leadership positions, and family income. Female students outperformed male respondents, while those who held class leadership positions and individuals from higher family income levels achieved better academic results.Surprisingly, lower-grade respondents exhibited a stronger approach goal orientation compared to higher-grade respondents.